Low wireless power transfer using inductive coupling for remote control car charger with indicator - Hamdan, Mohamad Hafizzudin; Mohd Asry, Anis Maisarah; Mustafa, Farahiyah (FAZ Publishing, 2020)
Wireless power transfer (WPT), in which electric power is transmitted through the overlapping magnetic fields of a transmitter and a receiver without the need for interconnecting wires, has widely researched in recent years. Nowadays, the main WPT method are developed based on the inductive coupling method. Inductively coupled chargers are being used for wireless charging of mobile phones, MP3 Player and other handheld devices. In this study, the concept of wireless power transfer using inductive coupling was applied to charge the remote control car. This study included the indicator to show the battery level. The output voltage of receiver is fixed at 15 Vdc to charge the battery with voltage of 7.2 Vdc. The battery takes around one and half hours to fully charge at maximum voltage up to 8.4 V. The efficiency of the charger to charge the battery approximately like the normal wired charger battery. The wireless power transfer was successfully developed and can be used to charge the battery remote control car freely without any connecting wire inserted. The wireless power transfer concept is a good concept to apply for electrical appliance at home and office in order to reduce the use of wire and also can increase the safety during handling the electrical devices.